2022
DOI: 10.3389/fimmu.2022.760776
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and Comparative Measures of Serum Chitotriosidase and YKL-40 in Patients With Idiopathic Pulmonary Fibrosis

Abstract: BackgroundAlthough chitin is absent in humans, chitinases are present in healthy subjects and show dysregulated expression in a variety of diseases resulting from abnormal tissue injury and repair responses. It was shown that chitotriosidase (chitinase 1/CHIT1) and structurally-related chitinase 3-like 1 protein (CHI3L1/YKL-40) play important roles in the pathobiology of idiopathic pulmonary fibrosis (IPF), however little is known about their longitudinal serum levels and relationship to clinical measures in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…A systematic review conducted by Tong et al showed that YKL-40 serum levels were higher in patients with interstitial lung disease (ILD), which includes PF, than in the control group [ 125 ]. Similar results were also obtained by Majewski et al in which the YKL-40 serum concentration was statistically significantly higher in patients with idiopathic pulmonary fibrosis than in healthy people [ 126 ]. Early positive results of YKL-40 protein research, obtained in various lung diseases, have become the basis for the analysis of this parameter in patients with COVID-19.…”
Section: Pulmonary Fibrosis In the Course Of Sars-cov-2 Virus Infectionsupporting
confidence: 88%
“…A systematic review conducted by Tong et al showed that YKL-40 serum levels were higher in patients with interstitial lung disease (ILD), which includes PF, than in the control group [ 125 ]. Similar results were also obtained by Majewski et al in which the YKL-40 serum concentration was statistically significantly higher in patients with idiopathic pulmonary fibrosis than in healthy people [ 126 ]. Early positive results of YKL-40 protein research, obtained in various lung diseases, have become the basis for the analysis of this parameter in patients with COVID-19.…”
Section: Pulmonary Fibrosis In the Course Of Sars-cov-2 Virus Infectionsupporting
confidence: 88%
“…This assumption is based on the previously observed data about parasite development and pathogenicity, which revealed that the parasite induces acute inflammatory responses in the infected tissues and encysts in the muscular and neural tissues. On the other hand, previous studies have documented the major role of YKL-40 in the inflammatory reactions, tissue injuries, remodeling, and repair, 43,51,52 and polarization of Th2, 40,53,54 which are all from the induced changes and mechanisms during the infection and the conflict against the parasite invasion. In addition, as variety of cells, including macrophages, neutrophils, SMC and FLC, are known to secrete the YKL-40 40,41,55,56 and essentially engaged in fighting the parasite and inducing an immune response, 57,58 it has been expected that excessive secretion of…”
Section: Discussionmentioning
confidence: 95%
“…The YKL-40 has important functions in many biological processes. It plays a major role in the inflammatory reactions, tissue injury, remodeling, and repair, 43 and has a strong correlation with many diseases. 44 However, it is still unknown whether YKL-40 is markedly secreted in Toxoplasmosis or not and whether its level is different in the acute or chronic stage of the infection.…”
Section: While Chronic (Ongoing) Toxoplasmosis Is Usuallymentioning
confidence: 99%
“…Syndromic obesity was defined as the presence of dysmorphic features, organ malformations, hyperphagia, or cognitive delay in obese children with or without detected mutations or chromosomal abnormalities where, in most cases, an appropriate assent was not possible [36]. Previous studies had indicated changes in the CHIT1 activity in the presence of acute infections [37][38][39][40] and chronic inflammatory diseases [41][42][43][44][45]. Children homozygotes for dup24 who presented no CHIT1 activity [27,30] were also excluded.…”
Section: Patients and Clinical Variablesmentioning
confidence: 99%